2021
DOI: 10.3390/nu13124236
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Caffeine Consumption in New Zealand Tertiary Students

Abstract: Caffeine-related health incidents in New Zealand have escalated over the last two decades. In order to reduce the risk of substance-related harm, it is important to understand the consumers’ motivations for its use. This is especially true for tertiary students who are presumed to be at a higher risk due to seeking out caffeine’s well-known cognitive benefits as well as the targeted marketing of such products to young adults. This study examined the habits and motivations for caffeine consumption in tertiary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…However, it should be noted that in the present study, about 16% of consumers reported caffeine intake only from chocolate, a caffeine source that was not always considered in previous studies. In spite of this observation, the average daily caffeine consumption observed was similar to that found in previous studies focused on university students from different locations such as the US [6], New Zealand [24], Netherlands [5] and the European surveys examining similar age groups [2]. Furthermore, measured daily caffeine intake was also similar to a previous study performed by our research group in a cohort of slightly older participants from the same university (155.4 mg in the present vs. 164.3 mg in the previous study) [19].…”
Section: Discussionsupporting
confidence: 86%
“…However, it should be noted that in the present study, about 16% of consumers reported caffeine intake only from chocolate, a caffeine source that was not always considered in previous studies. In spite of this observation, the average daily caffeine consumption observed was similar to that found in previous studies focused on university students from different locations such as the US [6], New Zealand [24], Netherlands [5] and the European surveys examining similar age groups [2]. Furthermore, measured daily caffeine intake was also similar to a previous study performed by our research group in a cohort of slightly older participants from the same university (155.4 mg in the present vs. 164.3 mg in the previous study) [19].…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, coffeehouses allow people to fulfill their needs for social interaction and belonging in the community [ 13 ]. This situation is confirmed when the reasons why people consume caffeine are explored [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 82%
“…The studies-proven benefits of caffeine include increased alertness, endurance and attention, and combating fatigue. While these desirable effects are likely to potentiate caffeine consumption, adverse effects such as anxiety, irritability, and sleep disturbances may also appear to prevent additional or continued caffeine consumption (Stachyshyn et al 2021 ). It has been stated in the literature that caffeine can affect human health in both positive and negative ways.…”
Section: Discussionmentioning
confidence: 99%